Differences in protein expression among five species of stream stonefly (Plecoptera) along a latitudinal gradient in Japan. Issue 3 (19th September 2017) - Gamboa, Maribet; Tsuchiya, Maria Claret; Matsumoto, Suguru; Iwata, Hisato; Watanabe, Kozo
Abstract: Proteome variation among natural populations along an environmental gradient may provide insights into how the biological functions of species are related to their local adaptation. We investigated protein expression in five stream stonefly species from four geographic regions along a latitudinal gradient in Japan with varying climatic conditions. The extracted proteins were separated by two‐dimensional gel electrophoresis and identified by matrix‐assisted laser desorption/ionization of time‐of‐flight (MALDI TOF/TOF), yielding 446 proteins. Low interspecies variation in the proteome profiles was observed among five species within geographical regions, presumably due to the co‐occurring species sharing the environments. However, large spatial variations in protein expression were found among four geographic regions, suggesting strong regulation of protein expression in heterogeneous environments, where the spatial variations were positively correlated with water temperature. We identified 21 unique proteins expressed specifically in a geographical region and six common proteins expressed throughout all regions. In warmer regions, metabolic proteins were upregulated, whereas proteins related to cold stress, the photoperiod, and mating were downregulated. Oxygen‐related and energy‐production proteins were upregulated in colder regions with higher altitudes. Thus, our proteomic approach is useful for identifying and understanding important biological functions related to local adaptations by populations of stoneflies.